SPEECH ACTS IN DONALD TRUMP’S SPEECH: TRUMP BANS ALL REFUGEES AND CITIZENS OF 7 MAJORITY MUSLIM COUNTRIES ENTERING U.S - Euis Meinawati (XXXXXXXX, 2023)
Abstract. People surely know about Donald Trump. He is the elected president of U.S. on November 9th, 2016. Trump is considered a controversial person in every speech and action, it was attracting the writer to analyze his speech entitled Trump Bans All Refugees and Citizens of 7 Majority Muslim Countries Entering U.S., and the speech will be discussed linguistically by the writer. In analyzing Trump’s speech, the writer will relate it to the speech acts belong to J. L. Austin, those are: locutionary, illocutionary, and perlocutionary. The analysis that will be elaborated by the writer is about Austin’s types of speech acts contained in Donald Trump’s speech, and then the most and the least types used in Donald Trump’s speech, and also determining does perlocutionary is always exist in every Trump’s utterance. All analyzes will be elaborated using descriptive qualitative method. In this case, the writer found 10 utterances related to Donald Trump’s speech. In those utterances, there include 10 data of locutionary forces, 10 data of illocutionary forces, but only 2 data that show perlocutionary forces, because not all utterances conduct perlocutionary. Thus, every utterance can be linguistically analyzed, in order to see whether every speech always conduct perlocutionary forces or not.Keywords: Donald Trump, linguistics, speech, speech acts.